Introducing takaful in India: An exploratory study on acceptability, possibility and takaful model - Htay, Sheila Nu Nu; Salman, Syed Ahmed (2013)
Insurance has been widely used as a risk mitigation tool in our personal lives as well as in business world. It is not deniable that insurance has become part of parcel of our daily lives and it provides the benefits and protection to us when we are unfortunate. However, the concepts of riba (interest), gharar (uncertainty) and mysir (gambling) inherited in insurance principles and practices are prohibited from the Islamic perspective. The Muslim scholars introduced takful to replace the conventional insurance. Tremendously, takaful is at high growing rate and penetrating into both Muslim and Non-Muslim countries. However, to the extent of our knowledge, there are no takaful operators in India even though it has the second highest population and at the same time, third highest Muslim population in the world belongs to India. Thus, the aims of this study are to examine the acceptability and possibility of offering takaful in India and to propose the most suitable takaful model that should be engaged by the takaful operators and policy holders. The findings from 216 Muslim and 117 non-Muslim respondents show that acceptability of takaful by Indians regardless of Muslims or non-Muslims is very high and there is possibility that takaful products can be marketed in India. It seems regardless of the religion, takaful seems to be accepted by Indians. Moreover, 10 Shari’ah scholars 7 takaful operators and 5 consultants opine that hybrid model, i.e. the combined concept of wakalah and mudarabah, will be the most suitable model for India. Hence, future research should examine the perception of regulators to introduce takaful and economic viability of the proposed model.